Tell Me, Mom - Tagidi, Ima (Israel, 2009)
A portrait of the director Ima Tagidi's mother, and the story of a daughter trying to connect or re-connect to the mother through film.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films